La enseñanza del Derecho de la Unión Europea en España - Álvarez, Gonzalo (2011)
"This research was carried out within the framework of the project 'Teaching Regional Integration Law, a comparative perspective: Spain-Argentina' under the René Hugo Thalmann Scholarship Program for Training and Development of Human Resources for the Improvement of the Quality of Teaching and Research, of the University of Buenos Aires," Abstract translation by Sol Blanco Granada. -- The present work explores the teaching of the European Union law in Spain. What is taught, who taught it, how is taught. Its aim of study is the teaching of this discipline in Spain, although is written for Argentina. It seeks to provide information that contributes the strengthening of regional integration law, a long-standing field of study but of limited presence in most Argentine universities curricula.